2009
DOI: 10.1111/j.1470-6431.2009.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal foods and climate change: shadowing eating practices

Abstract: Animal farming exceeds all forms of transport in terms of global greenhouse gas (GHG) emissions. Despite the implications of the seriousness of addressing animal farming in relation to mitigating the effects of GHG emissions, to date, the relationship between consumer behaviour and climate change has tended to neglect the role of animal foods. This paper reports on a pilot study in which six UK households were ‘shadowed’ to facilitate the investigation of the relationship between animal food practices and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although environmental concerns are often cited as one of the main reasons driving consumer demand for alternative proteins, research has shown that only a minority of consumers are aware of and motivated by environmental concerns related to food production, in their desire to reduce meat consumption [ 11 , 125 , 126 , 127 ]. A recent systematic review of 34 studies found that only 13 to 26% of consumers were willing to stop or significantly reduce their meat consumption for environmental reasons, or have already changed their meat intake for environmental concerns [ 10 , 34 ].…”
Section: Summary Of Evidence On the Motivations To Consume Alternamentioning
confidence: 99%
“…Although environmental concerns are often cited as one of the main reasons driving consumer demand for alternative proteins, research has shown that only a minority of consumers are aware of and motivated by environmental concerns related to food production, in their desire to reduce meat consumption [ 11 , 125 , 126 , 127 ]. A recent systematic review of 34 studies found that only 13 to 26% of consumers were willing to stop or significantly reduce their meat consumption for environmental reasons, or have already changed their meat intake for environmental concerns [ 10 , 34 ].…”
Section: Summary Of Evidence On the Motivations To Consume Alternamentioning
confidence: 99%
“…A common finding in the literature is that relatively few consumers have developed certain awareness of the environmental impacts of meat consumption. Consumers often underestimate the impacts of meat consumption on climate change compared to other actions such as recycling, favouring local, organic and seasonal foods, and reducing food waste and excessive packaging, and express scepticism of scientific evidence linking meat and climate change [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. This limited knowledge functions as a barrier since knowledge about the negative environmental impact of meat consumption is associated with higher willingness to change meat consumption behaviour [53][54][55].…”
Section: Prior Topical Research: Factors Influencing Environmentally mentioning
confidence: 99%
“…All participants reported that they eat meats and vegetables in accordance with a typical Norwegian consumption pattern. The 24 participants were placed in four focus groups categorized by age, gender and marital status (single women 25-35, single men 25-35, married women 36-45 and married men [36][37][38][39][40][41][42][43][44][45]. See Table A4 in Appendix C for detailed information about the participants.…”
Section: Focus Group Interviewsmentioning
confidence: 99%
“…Anxieties are spreading about the dubious nutritional properties of 'junk food', about overeating and keeping control of weight, and about the long-term unknown and disquieting implications of eating GM foods. Moreover, whilst the intensification of animal breeding and rearing has made meat and animal products cheaper and more accessible to the vast majority of 'Westerners', the environmental consequences of intensive animal farming and the slaughter and suffering of farm animals, has raised new issues about the ethics of eating the flesh or other products of animals' bodies (Stuart, 2009;Cole et al, 2009). These concerns are not entirely new, and in antiquity (for example, in Greek philosophy and in the writings of the political and intellectual elites of the Roman Empire) there are many examples that emphasize that what we eat and how we eat, is part of how we should live a 'virtuous' life.…”
Section: Introductionmentioning
confidence: 98%